Anatomical relationship between the accessory process of the lumbar spine and the pedicle screw entry point. Issue 1 (26th August 2020) - Kanawati, Andrew J.; Fernandes, Renan J. R.; Gee, Aaron; Urquhart, Jennifer; Rasoulinejad, Parham; S. Bailey, Chris
Abstract: Introduction: The vertebra accessory process (or tubercle) of the lumbar spine is an understated landmark which lies caudal to the mammillary process at the base of the transverse process. To our knowledge, no studies compare its relation to pedicle entry point for screw placement. We proposed to evaluate whether a valid and reliable relationship exists between the accessory process and the projected pedicle axis. Material and Methods: The distance between the tip of the accessory process and the entry point of the pedicle screw was measured for 50 pedicles. The angle between this axis and the midline was measured. Interrater reliability was assessed intraclass correlation coefficient for two raters. Statistical analysis of the results was performed using SPSS. Results: The mean distance between the tip of accessory process and pedicle screw entry point was 6.58 mm ( SD ±2.05), and the mean angle between this axis and the midline was 29.4° medial ( SD ±10.08). The ICC for the two raters for the mean distance and the mean angle was 0.974 and 0.894. The calculated mean distance between the tip of the accessory process and pedicle screw entry point was 3.2 mm ( SD ±1.3) and 5.7 mm ( SD ±1.9) medial and cranial respectively. Conclusions: The accessory process is a consistent and reliable landmark to guide pedicle screw entry point, and compliments other screw insertion techniques. To our knowledge, this is the first study in the published literature to assess this relationship.